2021
DOI: 10.1093/jamia/ocab236
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis prediction, early detection, and identification using clinical text for machine learning: a systematic review

Abstract: Objective To determine the effects of using unstructured clinical text in machine learning (ML) for prediction, early detection, and identification of sepsis. Materials and methods PubMed, Scopus, ACM DL, dblp, and IEEE Xplore databases were searched. Articles utilizing clinical text for ML or natural language processing (NLP) to detect, identify, recognize, diagnose, or predict the onset, development, progress, or prognosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 140 publications
0
28
0
3
Order By: Relevance
“…This demonstrates that the text data available in the EHR is a source of valuable information able to improve model performance in addition to structured data. Yan et al 14 found comparable results in a review of 9 studies predicting sepsis. Although on average text-based models did not outperform structured-data models, we did see an interesting difference between clinical settings.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This demonstrates that the text data available in the EHR is a source of valuable information able to improve model performance in addition to structured data. Yan et al 14 found comparable results in a review of 9 studies predicting sepsis. Although on average text-based models did not outperform structured-data models, we did see an interesting difference between clinical settings.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, Yang et al 13 performed a large review of 579 prognostic prediction models, expanding on the review by Goldstein et al, 2 but neither focused on the use of text data. Another review, by Yan et al 14 studied the use of unstructured text in, specifically, early sepsis prediction. To our knowledge, no broad systematic review has been conducted on the development of text-based prognostic prediction models.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent review found over 1800 published studies of AI programs developed to predict sepsis in patients hospitalized or in the emergency room. However, none of these models have been widely adopted 11 . The resulting vacuum has been filled by a large commercial EHR vendor that developed its own proprietary model which it deployed to hundreds of US hospitals without any published critical evaluation 10 .…”
Section: Artificial Intelligence and Patient Safetymentioning
confidence: 99%
“…The prediction of sepsis for inpatients, a common condition with a high mortality rate, is an area of intense AI focus in health care [10][11][12] . Many studies have shown early detection and treatment of patients with sepsis can markedly reduce mortality.…”
Section: Artificial Intelligence and Patient Safetymentioning
confidence: 99%
“…There was a evidence that early identification and diagnosis were critical, and appropriate interventions can significantly improve the prognosis of patients with sepsis ( 4 , 5 ). However, due to the complex pathophysiological conditions of sepsis, individual differences, and delayed laboratory results, it often leads to the lack of early detection and treatment of sepsis ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%